Improvised Media for In Vitro Pollen Germination of some Species of Apocynaceae - Chatterjee, Reshmi; Sarkar, Satadip; Rao, GM Narasimha (International Journal of Environment, 2014)
Pollen germination forms one of the most important stage post pollination prior to fertilization. This is essential for proper seed setting and seed development. In vitro pollen germination test is the most reliable way of assessing the pollen viability. In the present study pollen grains of seven genera under Apocynaceae family namely, Allamanda, Alstonia, Catharanthus, Nerium, Plumeria, Thevetia and Tabernaemontana were tested in some basic cultural media, such as Brewbaker’s media, 6% Glucose solution, 4% Calcium Nitrate solution and 3% Boron solution. Alstonia pollen grains exhibited highest percentage of germination rate in all the cultural media. Glucose and Brewbaker’s media is found to be highly suitable for efficient pollen germination in all the genera. Boron solution is effective for germination of pollen grains of tree species. In vitro pollen germination can be easily carried out in laboratories. These results can be utilised in plant breeding programmes to improve cultivar and varieties. DOI: http://dx.doi.org/10.3126/ije.v3i3.11074 International Journal of Environment Vol.3(3) 2014: 146-153